TABOOS AND VULGARISMS IN THE POETIC WORKS OF FARIDA AFRUZ AS A MEANS OF INGREASING EXPRESSIVENESS (Scientific journal of the Fergana State University, 2023)
In this article, taboos and vulgarisms are interpreted as means vivid stylistics which  create expressiveness in the artistic text. As a rule, tabu and vulgarisms, which are not related to the belles-lettres, are studied as the means of expression of the author’s individual style, proved by commenting on the example of Farida Afruz’s poetic works.